Pengaruh Penurunan Aktivitas Cobalt-57 Terhadap QC (Quality Control) Harian SPECT (Single Photon Emission Computed Tomography) di Instalasi Kedokteran Nuklir RSUD A. W Sjahranie Samarinda - Khalisha, Siti Nur; Zurma, Retno; Putri, Erlinda Ratnasari; Munir, Rahmawati; Intifadhah, Sahara Hamas (Progressive Physics Journal, 2023)
The utilization of radiation in the field of nuclear medicine uses several main tools, one of them is the gamma camera. In its use, the gamma camera must always be in prime condition in accordance with the regulation of the Badan Pengawas Tenaga Nuklir (BAPETEN) No. 17 of 2012. To ensure that the gamma camera is always in prime condition, it is necessary to carry out several QCs (Quality Control) within a certain period of time with reference to international standards and recommendations from manufacturers. QC results show the measured value still within the required range (acceptance criteria), so it can be said that the gamma camera is in prime condition and ready to be used. The Nuclear Medicine Installation of RSUD A. W Sjahranie Samarinda use Cobalt-57 flood source plates to measure extrinsic uniformity during daily QC. This study used data in the form of tables of extrinsic calibration measurements and verification measurements as well as graphs of Cobalt-57 activity against QC time with extrinsic calibration methods and verification measurements were shown in this study. The conclusion is the lower the activity, the longer the QC times. Besides, the QC times based on the extrinsic callibration and verification measurements are not much different.